2018
DOI: 10.4067/s0716-10182018000600658
|View full text |Cite
|
Sign up to set email alerts
|

Co-infección por los virus del dengue y chikungunya. Revisión narrativa

Abstract: Los autores no registran conflicto de interés alguno en este artículo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Models to predict the dynamic of a vector disease based only environmental variables, has the challenge of the introduction and reintroduction of different dengue serotypes or genotype, during the study period, could also influence the increment of Dengue cases [7], as well as the introduction of other arboviruses like Zika in 2015 and Chikungunya in 2014, that are transmitted by same vector and cause a similar clinical disease [41,42] The results of this study shows that climatic variables could be important factors to predict Dengue incidence behavior, especially those whom affected the Aedes infestation index. It was observed that incidence of Dengue cases increased around of 7-8 weeks after raining season begins, similar to what Vargas et al [43], and Diaz et al [44], reported previously.…”
Section: Discussionsupporting
confidence: 89%
“…Models to predict the dynamic of a vector disease based only environmental variables, has the challenge of the introduction and reintroduction of different dengue serotypes or genotype, during the study period, could also influence the increment of Dengue cases [7], as well as the introduction of other arboviruses like Zika in 2015 and Chikungunya in 2014, that are transmitted by same vector and cause a similar clinical disease [41,42] The results of this study shows that climatic variables could be important factors to predict Dengue incidence behavior, especially those whom affected the Aedes infestation index. It was observed that incidence of Dengue cases increased around of 7-8 weeks after raining season begins, similar to what Vargas et al [43], and Diaz et al [44], reported previously.…”
Section: Discussionsupporting
confidence: 89%
“…Because of the wide CHIKV circulation in areas where DENV has been steadily circulating and transmitting, cases of DENV-CHIKV coinfections have been frequently reported (Caron et al, 2012;Calvo et al, 2016;Vargas et al, 2018;Rückert et al, 2017;Mercado-Reyes et al, 2019), although there is no evidence of a higher severity in these DENV-CHIKV coinfection cases. The national surveillance study performed in Colombia during the 2016 Zika virus (ZIKV) epidemic found 34 cases of coinfection (0.14%), most of them with CHIKV-ZIKV coinfections, and only three DENV-CHIKV coinfections with two deaths (Mercado et al, 2018;Rueda et al, 2019); however, in 2018 and 2019, the Colombian Ministry of Health reported a decrease in CHIKV cases (800) in each year (24% confirmed by laboratory), and 1% of these cases originated from the province of Valle del Cauca (BES, 2018).…”
Section: Introductionmentioning
confidence: 99%